Distributed finite-time velocity-free attitude coordination control for spacecraft formations. (May 2016) - Zou, An-Min; de Ruiter, Anton H.J.; Kumar, Krishna Dev
Abstract: In this paper, the finite-time velocity-free attitude coordination control for spacecraft formation flying under an undirected communication graph is addressed. A finite-time observer is introduced to obtain an accurate estimation of unmeasurable angular velocity and a decentralized finite-time observer is employed to estimate the angular acceleration of the virtual leader. With the application of the finite-time observer, the decentralized finite-time observer, and the homogeneous method, a continuous distributed finite-time attitude coordination control law is designed for a group of spacecraft without requiring angular velocity measurements. A rigorous proof shows that semi-global finite-time stability of the overall closed-loop system can be achieved and the proposed velocity-free control law guarantees a group of spacecraft to simultaneously track a common time-varying reference attitude in finite time even when the reference attitude is available only to a subset of the group members. The performance of the control scheme derived here is illustrated through numerical simulations.